Electrical Characterization of Pantograph and Catenary Offline Under Train Operating Conditions Based on Improved Habedank Model and AT Power Supply Network - Like Pan; Hongchi Wang; Zhiqiang Yu; Tong Xing; Caizhi Yang; Yuan Yuan; Xiaohan Zhu; Jianxiang Sun; Xiaoyun Sun; Yuehua Cui; Tao Feng; Xudong Yi; et al. (IEEE Access)
Presently, with the increase in the operating speed of a train, the off-line phenomenon of its pantograph and the contact wire occurs intermittently, which affects the quality of its receiving current. In this paper, a distributed parameter-based Habedank arc model for a fully parallel AT power supply network is developed to examine the electrical characteristics under the typical operating conditions, including the normal travel and entry/exit stations. The incorporation of the train acceleration parameter facilitates further enhancement of the Habedank arc model and the equivalent dynamic resistance, also validating them. The results show that the off-line discharge arc voltage of the train pantograph and the locomotive voltage waveform during the overcurrent phase separation interval show a decreasing and increasing trend respectively when entering and leaving the station. Due to the nonlinear dynamic characteristics of the arc, the overall waveform contains many harmonics. The advantage of this model is that it is a simple, rapid, and highly accurate method for constructing an off-line discharge circuit model of the pantograph and catenary (PAC) under the working conditions. This paper introduces a novel approach to studying the electrical characteristics of the PAC discharge model with distributed parameters in a fully parallel AT power supply network. Also, it considers the effects of the operational conditions of the train, such as the entering and leaving stations, on the discharge characteristics. The research results of this paper can provide a reference for the identification of the electrical characteristics and protection of a PAC equipment during the operation of the train under the working conditions.